Physical and micro-nano-structure properties of chromium nitride coating deposited by RF sputtering using dynamic glancing angle deposition - Jimenez, M.J.M.; Antunes, V.; Cucatti, S.; Riul, A.; Zagonel, L.F.; Figueroa, C.A.; Wisnivesky, D.; Alvarez, F. (Surface & coatings technology, 2019)
The CrN films were grown by rf-magnetron sputtering using a dynamic glancing angle deposition technique. In this technique, the substrate oscillates in front of the sputtering target with an angular amplitude and frequency commanded by a Programmable Logic Controller. The purpose of this paper is to study the physical properties of the CrN coatings deposited on crystalline silicon by using a square and linear dependence on time of the angle of oscillation of the substrate. The angular dependence of the atoms impinging on the substrate during the oscillation modified the flux and momentum transference to the films, forming a columnar wavy-like periodic structure depending on the customized oscillatory function. The influence of the oscillation on the physical properties of the materials such as morphology, residual stress, nano-hardness, crystallite size and texture of the columnar multi-components are reported. The angular dependence of the deposition technique opens the possibility to control, according to the specific application, the nanostructure, the of the hard coatings, the periodicity of the columnar films, the deposition rate of each period as well as the uniformity of the thickness of the CrN films. The technique can be applied to other hard coatings as well (e.g., TiN, TiCN and TiAlN). The flux F of atoms arriving on the substrate has a F ~ cos φ dependence on the impinging angle φ of the precursors. Considering that the compressive stress in hard coatings deposition depends, among other things, on both the substrate external bias and deposition rate, the technique offers a potentially useful possibility to tailor the compressive stress as well, which will be the subject of further research and applications. •Nanostructured CrN films obtained by substrate oscillation in front of the sputtering target•Substrate angular φ(t) position (amplitude and frequency) commanded by software•Periodic columnar nanostructure due to time dependence of the precursors landing angles•Properties (grain size, hardness, stress, growth rate, morphology, texture) dependence on φ(t)